Temporal variation of microbial population in acclimation and start-up period of a thermophilic desulfurization biofilter. (April 2016) - Zhang, Jingying; Li, Lin; Liu, Junxin; Han, Yunping
Abstract: Microorganisms in a biofilter play important roles in the gas contaminants treatment process. In this study, thermophilic desulfurization bacteria were inoculated in a thermophilic biofilter for SO2 treatment after acclimation and enrichment. Molecular biology techniques were applied to detect temporal variation of microbial population during acclimation and biofilter start-up period. The acclimation temperatures were 50, 55, and 60 °C. Desulfurization bacteria dominated the enrichments. During acclimation, desulfurization bacteria and thermophilic bacteria increased from 36.84% to 78.95%–52.94% and 88.24%, respectively. In addition, the microbial diversity indices of these enrichments decreased with time. Substrate species and acclimation temperature influenced the microbial structure of the enrichments. The thermophilic biofilter inoculated with enrichments could achieve a rapid start-up, and over 80% of removal efficiency could be obtained within two weeks. The maximum elimination capacity was 38.71 g m −3  h −1 at 152 mg m −3 inlet concentration. The total sulfur bacteria proportion increased obviously during the start-up period. Moreover, desulfurization bacteria that originally existed in inocula, e.g., Pseudomonas putida, Bacillus thioparans, Microbacterium sp., and Thermoanaerobacteriaceae, were abundant in the thermophilic biofilter for SO2 removal. Highlights: Temporal variation of microbial population during acclimatization. Microbial characteristics in a thermophilic biofilter during the start-up period. The enrichment population relies on substrate species and acclimation temperature. Inoculation hastens acclimation and does not affect removal efficiency. Desulfurization and thermophilic bacteria dominated the biofilter after the start-up.